(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study investigates how local governments in China can promote collaborative innovation to enhance NPQ (New Product Quality) in the high-tech sports equipment industry. The findings suggest that local governments are actively creating opportunities for collaborative innovation by supporting initiatives that improve NPQ and expand access to high-value market opportunities. Through comparative case studies of Hangzhou and Shenzhen, the research reveals that Shenzhen’s policy framework is more inclusive and effective, largely due to its market-driven approach and strategic implementation of public-private partnership (PPP) models. These initiatives include the establishment of dedicated innovation parks designed to foster business-led NPQ improvements. Based on these insights, the study recommends that local governments should adapt their policies to local market conditions and environmental factors, as such could have a wider impact in terms of the achievement of NPQ benchmarks through collaborative innovation strategies.